Об упрощенном способе культивирования и длительном хранении трихомонад - Падченко, И.К. (Вестник зоологии, 1968)
A problem of prolonged preservation of pathogenic Protozoa is almost unsettled until now. The existing methods of culture preservation (freezing, lyophilization etc.) do not satisfy the requirements of the biological and medical science and practice because of their complexity. The proposed method permits the problem of simplified cultuvation and prolonged (more than 4 months) preservation of trichomonades without reinoculation to be solved in a quite different way. The trichomonades do not change their morpholo-gical peculiarities and physiological properties. Utilazation of Protozoa mobility under the conditions created by a device of the corresponding design at a temperature range optimal for trichomonades is a basis of the method. The Protozoa of the desired density and age are always contained in the device. This effective method of trichomonade cultivation is very simple and easy for any laboratory.